2011
DOI: 10.1177/003335491112600210
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Pregnancy Check Boxes on Death Certificates in Identifying Pregnancy-Associated Mortality

Abstract: SYNOPSISObjectives. Information that would allow the identification of women who were pregnant at the time of death or within the year preceding death has historically been underreported on death certificates. As a result, the magnitude of the problem of pregnancy-associated mortality is underestimated. To improve the identification of these deaths, check boxes for reporting pregnancy status have been added to death certificates in a number of states. We used multiple external data sources to determine whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 7 publications
1
26
0
Order By: Relevance
“…This is the exact inverse of the USA where no nationally comprehensive confidential enquiries have been completed (although some states have established maternal mortality review boards). The USA has high MMR for a high-SDI country—and is one of the few where it is increasing—but following the lead of Mexico and much of Latin America, it is also one of the only countries that has proactively improved its civil registration system with addition of a pregnancy checkbox on the standard death certificate,62 so it is possible that at least a portion of the increase is related to enhanced case ascertainment 62. The USA should learn from the experiences of other countries and consider implementing regular, comprehensive confidential enquiries into drivers of maternal mortality.…”
Section: Discussionmentioning
confidence: 99%
“…This is the exact inverse of the USA where no nationally comprehensive confidential enquiries have been completed (although some states have established maternal mortality review boards). The USA has high MMR for a high-SDI country—and is one of the few where it is increasing—but following the lead of Mexico and much of Latin America, it is also one of the only countries that has proactively improved its civil registration system with addition of a pregnancy checkbox on the standard death certificate,62 so it is possible that at least a portion of the increase is related to enhanced case ascertainment 62. The USA should learn from the experiences of other countries and consider implementing regular, comprehensive confidential enquiries into drivers of maternal mortality.…”
Section: Discussionmentioning
confidence: 99%
“…21 Likewise, pregnancy-associated suicide ratios were the number of suicides among pregnant or postpartum women divided by the number of live births from states and years included in this analysis. Given documented underreporting of pregnancy status on death records, 22 we acknowledge that these mortality ratios are underestimates of the true rates of homicide and suicide in the peripartum period; however, their purpose is to illustrate the difference in risk across maternal demographic characteristics. Therefore we present rate ratios (and 95% confidence intervals [CI]) for pregnancy-associated homicide and suicide by demographic characteristic rather than absolute rates.…”
Section: Methodsmentioning
confidence: 99%
“…Fildes et al reviewed medical examiner records from 1986–1989 in Cook County, IL and found that 65% of the deaths to women who were pregnant or postpartum were not identified as such on the death record. 8 More recently, Horon and Cheng 22 quantified the underreporting of pregnancy/postpartum status on death certificates from 2001–2008 in Maryland. It is important to note that the Maryland Department of Health and Mental Hygiene implemented enhanced surveillance of pregnancy-associated death on death records beginning in 2001, and the Maryland Maternal Mortality Review Committee – established in 2000 – performs a detailed case review, including review of medical examiner records and linkage of the women’s death certificates with birth and fetal death certificates from the prior year to enhance the accuracy of reporting.…”
Section: Methodsmentioning
confidence: 99%
“…[7][8][9] Furthermore, these rates are based on whether the death certificate records pregnancy or recent childbirth. Data from Europe suggest that underreporting of perinatal suicide on death certificates is in the range of 26% to 56%, 10,11 given that the presence of a child, or perhaps a birth, does not always emerge during the investigation of a death. 1,4,9,12,13 Despite high-profile media attention and calls to increase knowledge, with the goal of encouraging policy change, little is known about the true extent of the problem in Canada or the steps that can be taken to prevent it.…”
mentioning
confidence: 99%